The chimeric Onobrychis tenoreana (Fabaceae) and lectotypification of the names O. laconica and O. pentelica - Del Guacchio, Emanuele; Bernardo, Liliana; Iamonico, Duilio (Phytotaxa, 2021)
As part of ongoing studies on Fabaceae Lindl. (see e.g., Bernardo et al. 2019, Iberite et al. 2017, Iamonico et al. 2021), we here present a note about the names Onobrychis tenoreana Lacaita (1911: 276), O. laconica Orph. ex Boissier (1872–1873: 530) [= O. alba (Waldstein & Kitaibel 1803–1805: 111) Desvaux (1814: 83) subsp. pentelica (Haussknecht 1887: 71) Nyman (1889: 99)], and O. pentelica. The research is based on both analysis of the relevant literature and examination of specimens at BM, FI, JE, MPU, and P (Thiers 2021 onwards).